Mortality compression and variability in age at death in India - Suryakant Yadav; Arokiasamy Perianayagam (Comparative Population Studies (CPoS), 2020)
The global rise of life expectancy at birth has attracted worldwide interest, especially in understanding the pace of mortality transition in developing countries. In this study, we assess the progress of mortality transition in India during four decades between 1970 and 2013. We estimate measures of mortality compression and variability in age at death to assess the trends and patterns in mortality compression for India as a whole and its twelve biggest states. The results reveal an unequivocal convergence pattern in mortality compression across the states underpinned by the reduction in premature mortality and emerging homogeneity in mortality. Results by gender show that women are more homogenous in their mortality across the country because of an explicit reduction in the Gini coefficients at age 10 by the age group of 15-29 years. Mortality compression has changed in recent decades because of the increased survival of women in their reproductive ages, which marked a distinct phase of mortality transition in India. The pace of mortality transition, however, varies; adult mortality decline was greater than senescent mortality decline. These results show that India has passed the middle stage of mortality transition and has entered an early phase of low mortality.
urn:nbn:de:bib-cpos-2020-20en8
Keywords: 300; Mortality compression; Variability in age at death; Gini coefficient; Adult mortality; Premature mortality; Mortality transition